2023
DOI: 10.1002/mnfr.202200270
|View full text |Cite
|
Sign up to set email alerts
|

The Polymethoxyflavone Sudachitin Modulates the Circadian Clock and Improves Liver Physiology

Abstract: Scope Polymethoxylated flavones (PMFs) are a group of natural compounds known to display a wide array of beneficial effects to promote physiological fitness. Recent studies reveal circadian clocks as an important cellular mechanism mediating preventive efficacy of the major PMF Nobiletin against metabolic disorders. Sudachitin is a PMF enriched in Citrus sudachi, and its functions and mechanism of action are poorly understood. Methods and results Using circadian reporter cells, it shows that Sudachitin modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 67 publications
1
14
0
Order By: Relevance
“…The studies included in this review were published from 2008 to 2024, with the majority published after 2016, reflecting the growing scientific interest in (poly)phenols and circadian biology. Table 2 [ [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] ] summarizes the main characteristics and outcomes of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included in this review were published from 2008 to 2024, with the majority published after 2016, reflecting the growing scientific interest in (poly)phenols and circadian biology. Table 2 [ [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] , [96] , [97] , [98] , [99] , [100] , [101] , [102] , [103] , [104] , [105] , [106] , [107] , [108] , [109] ] summarizes the main characteristics and outcomes of the included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Intake of citrus peel polymethoxyflavones, such as sudachitin and nobiletin, prevents obesity in humans and rodents [25][26][27]40]. Nobiletin is known to promote lipolysis in adipocytes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Sudachitin exerts anti-obesogenic effects in rodents and humans [25][26][27]. A previous study demonstrated that sudachitin suppresses HFD-induced obesity by stimulating mitochondrial biogenesis in myocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also found in some citrus fruits, including Japanese mandarins, grapefruits, lemons (Citrus limon), and limes (Citrus aurantiifolia), as well as buckwheat (Fagopyrum esculentum), and is used as a vascular protection medication in many countries [26]. Recently, Sudachitin, which is present in Sudachi (Citrus Sudachi), has been shown to regulate circadian rhythm and suppress the accumulation of fat in the liver [27].…”
Section: Citrus Fruitsmentioning
confidence: 99%